RELATIONSHIP OF SERVICE RECOVERY TOWARDS PATIENT SATISFACTION IN HOSPITAL IN WEST SUMATERA - Semiarty, Rima; Machmud, Rizanda; Abdiana; Wahyuni, Annisa; Hamzah, Prima Kurniati (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
Background: Patient satisfaction in the M. Djamil Hospital was recorded as 79.61% between January and March 2018. It signifies that patient satisfaction rate has not met the target set of 85%. Aims: This study aims to determine the frequency distribution of service recovery patients, patient satisfaction, and the relationship between services and service recovery patient satisfaction to improve service recovery. Methods: The authors used a cross-sectional research design. The sample was inpatients at RSUP M. Djamil in total of 424 people. The sampling technique was consecutive sampling. The data were collected using the Importance Performance Analysis questionnaire. Data were analyzed using unpaired t-tests and multiple linear regression. Results: The results of the service recovery (distributive justice, procedure justice, interactive justice, reputation justice) has a significant relationship (p-value <0.05) with patient satisfaction. Interactive justice has the strongest relationship with appropriate patient satisfaction and has the greatest Beta value (0,254). Patient satisfaction has a significant relationship (p-value <0.05) with Word of Mouth. Conclusion: RSUP M. Djamil needs to emphasize interactions and justice, especially in providing clear information about medical actions to the patient's family, serving patients politely and friendly, and providing solutions to patients if there are service complaints. Keywords: Hospitalization, Satisfaction, Service Recovery